2008
DOI: 10.1007/s10511-008-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the conspicuous infrared star cluster and star-forming region “RCW 38 IR Cluster”

Abstract: The infrared star cluster RCW 38 IR Cluster, which is also a massive star-forming region, is investigated. The results of observations with the SEST (Cerro La Silla, Chile) telescope on the 2.6-mm 12 CO spectral line and with SIMBA on the 1.2-mm continuum are given. The 12 CO observations revealed the existence of several molecular clouds, two of which (clouds 1 and 2) are connected with the object RCW 38 IR Cluster. Cloud 1 is a massive cloud, which has a depression in which the investigated object is embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The finger cloud is not likely affected by self-absorption in 12 CO, since 12 CO and 13 CO show similar distributions in the declinationvelocity maps in Figures 3(c) and (f). We find three "bridging" 9 The two velocity features reported by Gyulbudaghian & May (2008) in 12 CO J = 1-0 correspond to the two peaks caused by self-absorption.…”
Section: Detailed Molecular Distributions With Mopra and Astementioning
confidence: 56%
See 1 more Smart Citation
“…The finger cloud is not likely affected by self-absorption in 12 CO, since 12 CO and 13 CO show similar distributions in the declinationvelocity maps in Figures 3(c) and (f). We find three "bridging" 9 The two velocity features reported by Gyulbudaghian & May (2008) in 12 CO J = 1-0 correspond to the two peaks caused by self-absorption.…”
Section: Detailed Molecular Distributions With Mopra and Astementioning
confidence: 56%
“…12 CO J = 1-0 observations with the SEST telescope at 45″ resolution for a small 160″×160″ region performed by Gyulbudaghian & May (2008) show two molecular clouds likely associated with RCW 38 in two different velocity ranges of −3 to +2 km s −1 and +3 to +8 km s −1 . In this paper, we present new molecular line observations toward RCW 38 obtained with NANTEN2, Mopra, and ASTE telescopes.…”
Section: Rcw 38 As the Youngest Super Star Cluster In The Milky Waymentioning
confidence: 96%
“…Figure 2d shows the distribution of the 12 CO J=1-0 emission observed with NANTEN, where the velocity range is −3 to +12 km s −1 . For the central 2 ′ × 2 ′ area, Gyulbudaghian & May (2008) showed that the two clouds of 12 CO J=1-0 emission with the velocity ranges of −3-+2 km s −1 and +3-+8 km s −1 are associated with RCW 38 from the Swedish-ESO Submillimetre Telescope (SEST) observation. Therefore the CO cloud shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2 In [16] it is supposed that these stars are early-type stars with dust discs, so that we can also suppose that the star N1 from Table 2 of this paper is an early-type star with dust envelope (or disc), and other stars from Tables 1 and 2 of this paper are late-type stars with dust discs (or envelopes).…”
Section: Spiral Jets Bright Nebula and A Group Of Embedded Stars Onmentioning
confidence: 99%